Conditional knockout of CRMP2 in neurons, but not astrocytes, disrupts spinal nociceptive neurotransmission to control the initiation and maintenance of chronic neuropathic pain. Issue 2 (17th May 2021) - Boinon, Lisa; Yu, Jie; Madura, Cynthia L.; Chefdeville, Aude; Feinstein, Douglas L.; Moutal, Aubin; Khanna, Rajesh
Abstract : Collapsin response mediator protein 2 is a key regulator of glutamatergic sensory neurotransmission that contributes to the initiation and maintenance of chronic neuropathic pain. Abstract: Mechanistic studies principally focusing on primary afferent nociceptive neurons uncovered the upregulation of collapsin response mediator protein 2 (CRMP2)—a dual trafficking regulator of N-type voltage-gated calcium (Cav 2.2) as well as Nav 1.7 voltage-gated sodium channels—as a potential determinant of neuropathic pain. Whether CRMP2 contributes to aberrant excitatory synaptic transmission underlying neuropathic pain processing after peripheral nerve injury is unknown. Here, we interrogated CRMP2's role in synaptic transmission and in the initiation or maintenance of chronic pain. In rats, short-interfering RNA-mediated knockdown of CRMP2 in the spinal cord reduced the frequency and amplitude of spontaneous excitatory postsynaptic currents, but not spontaneous inhibitory postsynaptic currents, recorded from superficial dorsal horn neurons in acute spinal cord slices. No effect was observed on miniature excitatory postsynaptic currents and inhibitory postsynaptic currents. In a complementary targeted approach, conditional knockout of CRMP2 from mouse neurons using a calcium/calmodulin-dependent protein kinase II alpha promoter to drive Cre recombinase expression reduced the frequency and amplitude of spontaneous excitatory postsynaptic currents, but not miniature excitatory SCss. Conditional knockout of CRMP2 from mouse astrocytes using a glial fibrillary acidic protein promoter had no effect on synaptic transmission. Conditional knockout of CRMP2 in neurons reversed established mechanical allodynia induced by a spared nerve injury in both male and female mice. In addition, the development of spared nerve injury–induced allodynia was also prevented in these mice. Our data strongly suggest that CRMP2 is a key regulator of glutamatergic neurotransmission driving pain signaling and that it contributes to the transition of physiological pain into pathological pain.